Evolutionary Approach to Infrastructure Formation in Russia’s Economic Systems with Using Supply Chain Management Strategy for the Mineral Raw Material Specialization - Luebeck, Ju.V (International Journal of Supply Chain Management, 2019)
The article presents the theoretical framework for the infrastructure formation in the economic systems specializing in mineral raw materials, by using supply chain strategy. It is determined by objective processes of economic development and sect oral peculiarities, in the form of synthesis of reproduction, structural-functional and systemic approaches in supply chain management. It allows developing adequate mechanisms aimed at maintaining and further developing infrastructure of territorial economic systems (TES).